Positive electrode lead paste for deep-discharge high-cycle lead storage battery and preparation method of positive electrode lead paste
By adding porous carbon microbeads, carbon whiskers, white carbon black and sodium carboxymethylcellulose into the positive lead paste of lead batteries, the problem of short service life of existing lead batteries in deep discharge and high circulation use is solved, and a higher cycle life and deep discharge capacity are achieved.
Patent Information
- Application Number
- CN202411506439.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-07
AI Technical Summary
The positive lead paste and preparation methods of existing lead-acid batteries cannot meet the requirements of deep discharge and high recycling, resulting in a short service life and a low specific energy.
Add porous carbon microbeads, carbon whiskers, white carbon black and sodium carboxymethylcellulose to the positive electrode lead paste. The positive electrode lead paste with a porous structure is prepared by optimizing process conditions such as ultrasonic emulsification and high-speed shear mixing.
It extends the time for the softening of active substances, improves the service life of the battery, and enhances the deep discharge and high circulation capabilities of the battery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a positive lead paste for a deep-discharge high-cycle lead-acid battery and a preparation method thereof. Background Art
[0002] Lead-acid batteries have gone through 160 years of development since they were invented in 1859. Although they are facing challenges from new secondary power sources, they still occupy a place in the secondary power market due to their excellent safety, low manufacturing cost, and nearly 100% recycling and utilization. However, short service life and low specific energy are still the prominent disadvantages of lead-acid batteries.
[0003] The positive and negative plates are very critical components in the battery. The quality of the positive and negative plates directly determines the discharge capacity and cycle life of the battery. The positive electrode of the lead-acid battery is composed of grids and granular PbO2 (lead dioxide). During the discharge process, the lead dioxide undergoes a reduction reaction to form lead sulfate. The efficiency of the active substance in the conversion process affects the performance and quality of the battery, which is mainly affected by the lead paste formula. The existing lead paste for lead-acid batteries and its preparation method cannot meet the use requirements of energy storage lead-acid batteries.
[0004] Due to the characteristics of valve-regulated lead-acid batteries, the charging and discharging processes of electric vehicle batteries are affected by ambient temperature, usage habits, and matching chargers. Valve-regulated batteries are limited by the capacity of the positive plate and the electrolyte during the discharge process. The positive plate active substances and the negative electrode active substances undergo electrochemical conversion. The material formula and quality of the positive plate active substances are also necessary conditions for determining the battery capacity and cycle life.
[0005] The patent application with publication number CN113394400A discloses a negative lead paste, a negative plate and a lead-acid battery for a lead-acid battery, belonging to the technical field of lead-acid batteries. A negative lead paste for a lead-acid battery comprises lead powder and an additive, wherein the additive comprises the following components: based on the total lead powder mass, 0.9-1wt% of barium sulfate, 0.3-0.4wt% of acetylene black, 0.05-0.08wt% of lignin, 0.5-0.8wt% of humic acid, 0.07-0.08wt% of short fibers, 0.03-0.05wt% of nano-silica sol and 0.55-0.7wt% of sulfamic acid. The sulfamic acid added to the negative lead paste of the invention can increase the content of sulfate radicals in the negative lead paste, prevent the lead-acid battery from sulfation, and prevent the formation of dendrites; the synergistic effect of sulfamic acid and acetylene black is beneficial to prolonging the service life of the lead-acid battery.
[0006] The patent application with publication number CN116207251A discloses a positive lead paste, a positive plate and a lead-acid battery for a lead-acid battery, and relates to the technical field of lead-acid batteries. The present invention effectively suppresses the problem of rapid battery capacity decay and improves the positive charge and discharge capacity of the battery by adding a composite stabilizer aminosulfonic acid powder as a special additive to the positive electrode formula lead powder. The composite stabilizer aminosulfonic acid powder includes aminosulfonic acid powder and carbon aerogel. The formula is suitable for use in lead-acid valve-regulated electric vehicle power batteries. The positive plate made by this lead paste, in the performance test of the finished battery made by the same lead paste, the battery charge and discharge efficiency is improved by more than 2%, and the battery life cycle is improved by more than 28%. Summary of the invention
[0007] Based on the deficiencies in the prior art, the present invention provides a positive lead paste for a deep discharge high cycle lead-acid battery and a preparation method thereof. In this scheme, porous carbon microbeads, carbon whiskers, white carbon black and sodium carboxymethyl cellulose are added to the active material, which prolongs the softening time of the active material and the service life of the battery, making it more suitable for deep discharge and high cycle.
[0008] The specific technical solutions of the present invention are as follows:
[0009] The invention provides a positive lead paste for a deep-discharge high-cycle lead-acid battery. The positive lead paste comprises lead powder and additives. Based on 100 parts by weight of the lead powder, the additives comprise 0.05-0.2 parts of porous carbon microbeads, 0.08-0.15 parts of carbon whiskers, 0.5-1.5 parts of white carbon black, 0.3-1 parts of sodium carboxymethyl cellulose, 0.1-0.5 parts of sodium perborate, 0.1-0.5 parts of tetrabasic lead sulfate, 0.06-0.1 parts of stannous oxide, 0.08-0.15 parts of antimony trioxide and 0.08-0.15 parts of polyester staple fibers.
[0010] Specifically, based on 100 parts by weight of lead powder, the positive lead paste for deep discharge high cycle lead-acid battery further includes 10 to 12 parts of water and 8 to 11 parts of sulfuric acid with a density of 1.4 g / mL, wherein the water is pure water with a resistivity of ≤3 μS / cm.
[0011] (1) Sodium perborate: When the positive electrode active material contains boron, a certain chemical reaction will occur on the surface of lead, boron and alkaline earth metal lead alloy, which can improve the close contact performance between the active material and the grid, as well as the bonding performance between the active materials. Sodium perborate will decompose in humid air or when slightly heated, and release oxygen. Adding it to lead paste is conducive to the formation of PbO and reduces the content of free lead.
[0012] (2) Tetrabasic lead sulfate 4BS: 4BS seed crystals are introduced into the positive electrode raw materials as additives. 4BS seed crystals can induce the formation of fine and uniform 4BS particles in the plate, which can greatly improve the consistency of plate performance. With the 75°C high-temperature curing process, the 4BS content in the green plate can be increased to 75%, and the free lead oxidation efficiency is higher. The introduction of 4BS seed crystals can also increase the porosity of the lead paste to 46.6%, which is conducive to the entry of oxygen into the lead paste, making curing easier and enhancing the bonding force between the active substances of the plate. By optimizing the formation process, the battery life is ultimately extended.
[0013] (3) Stannous oxide: (chemical formula SnO, formula weight 134.7), also known as tin monoxide, is soluble in dilute sulfuric acid to form stannous salt. Stannous oxide is added during the paste mixing process. After the battery is acidified, it reacts with dilute sulfuric acid to form stannous sulfate. Stannous sulfate is oxidized to tin dioxide during charging. Both tin dioxide and β-PbO2 have diamond structures and have good electrical conductivity, which can improve the utilization rate of the positive electrode active material.
[0014] (4) Antimony trioxide is used as an additive for the positive plate active material. It is added to the lead powder of the paste to eliminate the "antimony-free effect". During the battery charging process, oxygen is precipitated on the surface of the positive grid, and the interface between the grid and the active material is oxidized. There are PbO and PbO2 in the oxidized corrosion layer. The resistance of PbO is very large. If a large amount of PbO is generated, it will seriously affect the electrode reaction. During charging and discharging, heat is generated at the interface between the grid and the active material, causing the interface between the grid and the active material to deteriorate. Antimony ions can promote the positive active material (lead paste) to maintain the crystal bond between α-PbO2 and β-PbO2. At the same time, the corrosion product of Sb is a nucleation catalyst for β-PbO2, which adheres to the surface of the grid, making the PbO2 particles at the grid interface refined, thereby improving the electrochemical capacity and deep cycle life.
[0015] (5) White carbon black is a general term for white powdered X-ray amorphous silicic acid and silicate products, mainly referring to precipitated silica, fumed silica and ultrafine silica gel. White carbon black is a porous substance, and its composition can be expressed by SiO2·nH2O, where nH2O exists in the form of surface hydroxyl groups and is insoluble in water and sulfuric acid. Because of its porosity, it can store local sulfuric acid solution, which can increase the capacity of the battery without affecting the life. The ultrafine nanometer scale used in the embodiment of the present invention has a size range of 1 to 100 nm.
[0016] (6) Sodium carboxymethyl cellulose (CMC) generates tiny pores in the active material, which can increase the initial capacity of the battery. It is also a liquid stabilizer for white carbon black.
[0017] (7) Porous carbon microbeads (also called micro-nano carbon spheres) are emerging nanocarbon materials after fullerenes and micro-nano carbon tubes. Micro-nano carbon spheres have low density (less than 2.6 g / cm 3 ), ultra-high specific surface area, high stacking density, chemical inertness, rich functional groups on the surface, stable physical and chemical properties, special structure, can be used as a material carrier and composite material reinforcement, the diameter of the carbon microbeads is above 11μm.
[0018] (8) Carbon whisker (graphite whisker) is also called graphite whisker. It has a hexagonal network stacking structure of carbon-carbon atoms. It has low apparent density, high specific strength and specific elastic modulus, and has excellent corrosion resistance and electrical conductivity.
[0019] The present invention also provides a method for preparing the positive lead paste for deep discharge high cycle lead storage battery, comprising the following steps:
[0020] (1) dissolving sodium perborate, tetrabasic lead sulfate, stannous oxide, and antimony trioxide in a first dose of water, and homogenously mixing to obtain a first homogenous mixed solution with a particle size of less than 1 μm, so as to improve the dispersibility of the additive during use;
[0021] (2) dissolving the porous carbon microbeads, white carbon black, sodium carboxymethyl cellulose, and carbon whiskers in a second dose of sulfuric acid, and mixing them uniformly to obtain a second homogeneous mixed solution;
[0022] (3) After dry-mixing the lead powder and polyester staple fibers, add a third dose of water, then add the first homogenous mixed liquid and mix evenly under vacuum, then add the second homogenous mixed liquid and a fourth dose of sulfuric acid, mix evenly to produce a paste.
[0023] Specifically, in step (1), an ultrasonic emulsifier is used for homogenous mixing; during homogenous mixing, the parameters set for the ultrasonic emulsifier are: ultrasonic emulsifier frequency 20-40KHZ, amplitude range 50-80μm, cavitation intensity 3-5W / cm 2 , power 1000~3000W;
[0024] The homogenous mixing temperature is 50-70° C., and the homogenous mixing time is 30-60 min.
[0025] Specifically, in step (2), a high-speed shearing machine is used for uniform mixing. During mixing, the mixing temperature is 50 to 70° C., the high-speed shearing machine is maintained at a rotation speed of 2500 to 3500 rpm, and high-speed shearing is performed for 150 to 250 minutes.
[0026] Specifically, in step (3), the pressure of the vacuum state is 0.05-0.06 MPa;
[0027] The paste temperature is not higher than 45℃.
[0028] Normal atmospheric pressure is 0.1Mpa. The 0.05-0.06Mpa here is a semi-vacuum state. In the semi-vacuum state, the boiling point of water is reduced, and the boiling point is about 66-69°C. Lowering the boiling point is equivalent to lowering the vaporization temperature of water. As the water evaporates, it takes away the heat generated by the paste, thereby achieving the purpose of temperature control.
[0029] In step (3), the specific steps are as follows: add 100 parts of lead powder and 0.08-0.15 parts of polyester staple fiber into the paste making machine, close the paste making machine, and then dry-mix and stir for 3 minutes, then pour in 8-10 parts of pure water for 3 minutes, then pour in a water-based emulsion for 3 minutes, and continue to stir for 2 minutes after the addition, and at the same time, the paste making machine starts to evacuate, and the pressure is controlled at 0.05-0.06Mpa, and then pour in an acid emulsion for 5 minutes, and then pour in 6-9 parts of dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste making work can be completed when the lead paste temperature is lower than 45 degrees.
[0030] Specifically, the volume ratio of the first dose in step (1) to the third dose in step (3) is 2:8-10;
[0031] The volume ratio of the second dose in step (2) to the fourth dose in step (3) is 2:6-9.
[0032] The present invention also provides a positive electrode plate for a deep discharge high cycle lead-acid battery, and uses the positive electrode lead paste for the deep discharge high cycle lead-acid battery.
[0033] The present invention also provides a lead-acid battery, comprising a positive plate, a negative plate, a separator and an electrolyte, wherein the positive plate is the positive plate for the deep-discharge high-cycle lead-acid battery.
[0034] Beneficial effects of the present invention:
[0035] (1) Porous carbon microbeads are a new type of nano-scale carbon material with ultra-high conductivity. In the microstructure of the active material, due to its porous characteristics, the active material crystallizes on the porous carbon microbeads to form branches during the charge and discharge process. Due to its conductivity, multiple branches crystallize around the carbon microbeads to form branch clusters. The charge and discharge cycle process is a process of shortening the branches. The branch clusters with the porous carbon microbeads as the center of the process delay the time for the branches to shorten during the charge and discharge process, apparently prolonging the time for the active material to soften, and prolonging the service life of the battery.
[0036] (2) Carbon whiskers have excellent electrical conductivity and high elastic strength. Compared with previous carbon fibers, they are thinner, shorter, and stronger. They are easier to disperse in active materials, thereby improving the strength and life of the active materials.
[0037] (3) White carbon black and sodium carboxymethyl cellulose (CMC), both substances have porous structures. When added to the active material, they increase the storage space of the electrolyte, thereby increasing the capacity and discharge depth of the plate. Since white carbon black and sodium carboxymethyl cellulose (CMC) do not participate in chemical reactions, the porous structure is maintained throughout the life cycle of the plate, providing a high storage space for the electrolyte for the plate reaction. Adequate electrolyte supply makes the battery more suitable for deep discharge, and the stable porous structure ensures the long life of the plate. The addition of white carbon black and sodium carboxymethyl cellulose (CMC) makes the plate more suitable for deep discharge and high cycle. DETAILED DESCRIPTION
[0038] Example 1
[0039] (1) Preparation of water-based emulsion
[0040] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.2kg sodium perborate, 0.2kg tetrabasic lead sulfate 4BS, 0.06kg stannous oxide, 0.08kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 20KHZ, the amplitude range is 50μm, and the cavitation intensity is 3W / cm 2 , power 1500W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 50℃ during cavitation mixing, the cavitation time is 30 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0041] (2) Preparation of acid-based emulsion
[0042] 0.05kg of porous carbon microbeads (diameter 1-2nm, pore size ≤2nm), 0.5kg of nano-white carbon black (particle size 1-100nm), 0.3kg of sodium carboxymethyl cellulose CMC, and 0.08kg of highly graphitized carbon whiskers (fiber diameter between 30 and 60μm, length 3-5mm) were added into an ultrasonic high-speed shearing machine, and then 2kg of dilute sulfuric acid liquid (density 1.4g / mL) was added. The high-speed shearing machine maintained a speed of 2500rpm, the mixed liquid was maintained at 50°C, and ultrasonic high-speed shearing was performed for 150min to obtain a homogeneous mixed emulsion.
[0043] (3) And paste process
[0044] Add 100kg lead powder and 0.08kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 8kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.05Mpa, then pour in acid emulsion for 5 minutes, then pour in 6kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0045] Example 2
[0046] (1) Preparation of water-based emulsion
[0047] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.5kg sodium perborate, 0.5kg tetrabasic lead sulfate 4BS, 0.1kg stannous oxide, 0.15kg antimony trioxide into the ultrasonic emulsifier mixer. The frequency of the ultrasonic emulsifier is 40KHZ, the amplitude range is 80μm, and the cavitation intensity is 5W / cm 2 , power 3000W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 70℃ during cavitation mixing, the cavitation time is 60 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0048] (2) Preparation of acid-based emulsion
[0049] 0.2kg of porous carbon microbeads (diameter 1-2nm, pore size ≤2nm), 1.5kg of nano-white carbon black (particle size 1-100nm), 1kg of sodium carboxymethyl cellulose CMC, and 0.15kg of highly graphitized carbon whiskers (fiber diameter between 30 and 60μm, length 3-5mm) were added into an ultrasonic high-speed shearing machine, and then 2kg of dilute sulfuric acid liquid (density 1.4g / mL) was added. The high-speed shearing machine maintained a speed of 3500rpm, the mixed liquid was maintained at 70°C, and ultrasonic high-speed shearing was performed for 250min to obtain a homogeneous mixed emulsion.
[0050] (3) And paste process
[0051] Add 100kg lead powder and 0.15kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 10kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.06Mpa, then pour in acid emulsion for 5 minutes, then pour in 9kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0052] Example 3
[0053] (1) Preparation of water-based emulsion
[0054] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.3kg sodium perborate, 0.3kg tetrabasic lead sulfate 4BS, 0.08kg stannous oxide, 0.1kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 30KHZ, the amplitude range is 65μm, and the cavitation intensity is 4W / cm 2 , power 2000W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 60℃ during cavitation mixing, the cavitation time is 45 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0055] (2) Preparation of acid-based emulsion
[0056] 0.1 kg of porous carbon microbeads (diameter 1-2 nm, pore size ≤ 2 nm), 1 kg of nano-white carbon black (particle size 1-100 nm), 0.8 kg of sodium carboxymethyl cellulose CMC, and 0.1 kg of highly graphitized carbon whiskers (fiber diameter between 30 and 60 μm, length 3-5 mm) were added into an ultrasonic high-speed shearing machine, and then 2 kg of dilute sulfuric acid liquid (density 1.4 g / mL) was added. The high-speed shearing machine was maintained at a speed of 3000 rpm, the mixed liquid was maintained at 60° C., and ultrasonic high-speed shearing was performed for 200 minutes to obtain a homogeneous mixed emulsion.
[0057] (3) And paste process
[0058] Add 100kg lead powder and 0.1kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 9kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.055Mpa, then pour in acid emulsion for 5 minutes, then pour in 8kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0059] Comparative Example 1 (without carbon whiskers)
[0060] (1) Preparation of water-based emulsion
[0061] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.3kg sodium perborate, 0.3kg tetrabasic lead sulfate 4BS, 0.08kg stannous oxide, 0.1kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 30KHZ, the amplitude range is 65μm, and the cavitation intensity is 4W / cm 2, power 2000W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 60℃ during cavitation mixing, the cavitation time is 45 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0062] (2) Preparation of acid-based emulsion
[0063] 0.1 kg of porous carbon microbeads (diameter 1-2 nm, pore size ≤ 2 nm), 1 kg of nano-white carbon black (particle size 1-100 nm), and 0.8 kg of sodium carboxymethyl cellulose CMC were added into an ultrasonic high-speed shearing machine, and then 2 kg of dilute sulfuric acid liquid (density 1.4 g / mL) was added. The high-speed shearing machine was maintained at a speed of 3000 rpm, the mixed liquid was maintained at 60° C., and ultrasonic high-speed shearing was performed for 200 minutes to obtain a homogeneous mixed emulsion.
[0064] (3) And paste process
[0065] Add 100kg lead powder and 0.1kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 9kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.055Mpa, then pour in acid emulsion for 5 minutes, then pour in 8kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0066] Comparative Example 2 (without porous carbon microbeads (pore diameter ≤ 2 nm))
[0067] (1) Preparation of water-based emulsion
[0068] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.3kg sodium perborate, 0.3kg tetrabasic lead sulfate 4BS, 0.08kg stannous oxide, 0.1kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 30KHZ, the amplitude range is 65μm, and the cavitation intensity is 4W / cm 2 , power 2000W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 60℃ during cavitation mixing, the cavitation time is 45 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0069] (2) Preparation of acid-based emulsion
[0070] 1 kg of nano-white carbon black (particle size of 1 to 100 nm), 0.8 kg of sodium carboxymethyl cellulose CMC, and 0.1 kg of highly graphitized carbon whiskers (fiber diameter between 30 and 60 μm and length of 3 to 5 mm) were added into an ultrasonic high-speed shearing machine, and then 2 kg of dilute sulfuric acid liquid (density of 1.4 g / mL) was added. The high-speed shearing machine was maintained at a speed of 3000 r / min, the mixed liquid was maintained at 60° C., and ultrasonic high-speed shearing was performed for 200 minutes to obtain a homogeneous mixed emulsion.
[0071] (3) And paste process
[0072] Add 100kg lead powder and 0.1kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 9kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.055Mpa, then pour in acid emulsion for 5 minutes, then pour in 8kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0073] Comparative Example 3 (without nano-white carbon black)
[0074] (1) Preparation of water-based emulsion
[0075] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.3kg sodium perborate, 0.3kg tetrabasic lead sulfate 4BS, 0.08kg stannous oxide, 0.1kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 30KHZ, the amplitude range is 65μm, and the cavitation intensity is 4W / cm 2 , power 2000W, use ultrasonic cavitation effect of ultrasound to homogenize and mix the materials, the temperature is kept at 60℃ during cavitation mixing, the cavitation time is 45 minutes, and after ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained.
[0076] (2) Preparation of acid-based emulsion
[0077] 0.1 kg of porous carbon microbeads (diameter 1-2 nm, pore size ≤ 2 nm), 0.8 kg of sodium carboxymethyl cellulose CMC, and 0.1 parts of highly graphitized carbon whiskers (fiber diameter between 30 and 60 μm, length 3-5 mm) were added into an ultrasonic high-speed shearing machine, and then 2 parts of dilute sulfuric acid liquid (density 1.4 g / mL) were added. The high-speed shearing machine was maintained at a speed of 3000 rpm, the mixed liquid was maintained at 60°C, and ultrasonic high-speed shearing was performed for 200 minutes to obtain a homogeneous mixed emulsion.
[0078] (3) And paste process
[0079] Add 100kg lead powder and 0.1kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 9kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.055Mpa, then pour in acid emulsion for 5 minutes, then pour in 8kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0080] Comparative Example 4 (without sodium carboxymethyl cellulose)
[0081] (1) Preparation of water-based emulsion
[0082] Take 2kg pure water (resistance conductivity ≤ 3μS / cm), add 0.3kg sodium perborate, 0.3kg tetrabasic lead sulfate 4BS, 0.08kg stannous oxide, 0.1kg antimony trioxide into the ultrasonic emulsifier mixer, the ultrasonic emulsifier frequency is 30KHZ, the amplitude range is 65μm, and the cavitation intensity is 4W / cm 2 , power 2000W, using ultrasonic cavitation effect of ultrasound to homogenize and mix the materials. The temperature during cavitation mixing is maintained at 60°C, and the cavitation time is 45 minutes. After ultrasonic homogenization and emulsification, a homogenous mixed liquid with particles less than 1μm is obtained, which improves the dispersibility of the additive during use.
[0083] (2) Preparation of acid-based emulsion
[0084] 0.1 kg of porous carbon microbeads (diameter 1-2 nm, pore size ≤ 2 nm), 1 kg of nano-white carbon black (particle size 1-100 nm), and 0.1 kg of highly graphitized carbon whiskers (fiber diameter between 30 and 60 μm, length 3-5 mm) were added into an ultrasonic high-speed shearing machine, and then 2 kg of dilute sulfuric acid liquid (density 1.4 g / mL) was added. The high-speed shearing machine was maintained at a speed of 3000 rpm, the mixed liquid was maintained at 60° C., and ultrasonic high-speed shearing was performed for 200 minutes to obtain a homogeneous mixed emulsion.
[0085] (3) And paste process
[0086] Add 100kg lead powder and 0.1kg polyester staple fiber into the paste machine, close the paste machine, and then dry mix for 3 minutes, then pour in 9kg pure water for 3 minutes, then pour in water-based emulsion for 3 minutes, and continue to stir for 2 minutes after adding. At the same time, the paste machine starts to evacuate, and the pressure is controlled at 0.055Mpa, then pour in acid emulsion for 5 minutes, then pour in 8kg dilute sulfuric acid for 5 minutes, and continue to stir for 10 minutes. The paste work can be completed when the lead paste temperature is lower than 45 degrees.
[0087] Test Example 1
[0088] The lead pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were used to prepare plates and assemble 6-DZF-12 power batteries. Testing was carried out in accordance with GB / T2219-2017 "Valve-regulated Lead-acid Batteries for Electric Power-Assisted Vehicles". The performance was compared with that of batteries produced by normal processes. The capacity, large current discharge performance and cycle life were mainly tested. The testing method was carried out according to the following method.
[0089] 1. Test items: 2h rate discharge: According to the national battery standard GB / T22199-20175.5, after the battery is fully charged, it is kept stationary for 1 to 24 hours in an environment with a temperature of 25±2℃, and discharged at a constant current of 6A. When the battery voltage is 10.5V, the 2h rate capacity C a The C2 standard should be reached within three cycles.
[0090] 2. High current discharge: According to the national battery standard GB / T22199-20175.5, after the battery is fully charged, it should be placed in an environment with a temperature of 25±5 for 1 to 4 hours, and then discharged at a current of 3.6I2(A) until the battery voltage reaches 10.5V. The discharge duration should be no less than 25min.
[0091] 3. Cycle life: According to the national battery standard GB / T22199-20175.12, in an environment with a temperature of 25±5℃, discharge at a current of 1.0I2(A) for 1.6h, and then charge at a constant voltage of 16V (current limit 0.4I2A) for 6.4h as one cycle. When the terminal voltage of the battery is lower than 10.5V for three consecutive times after discharging for 1.6h, the battery cycle life is terminated. The total cycle life is not less than 350 times.
[0092] The test results are shown in Table 1.
[0093] Table 1
[0094] Example 2h rate deep discharge capacity / min High current discharge / min Cycle life / times Example 1 133.2 33.3 422 Example 2 132.9 33.6 426 Example 3 133.6 33.5 428 Comparative Example 1 128.7 29.8 391 Comparative Example 2 127.8 29.7 394 Comparative Example 3 127.1 29.3 391 Comparative Example 4 127.3 29.6 394
[0095] It can be seen from the above table that the deep discharge capacity, large current discharge performance and cycle life of Example 1, Example 2 and Example 3 are significantly better than those of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, especially the cycle life is extended by more than 8%, indicating that the battery performance of the plate assembled by adding new substances carbon whiskers and porous carbon microbeads, nano-white carbon black and sodium carboxymethyl cellulose is excellent. Through data comparison, it is comprehensively explained that the present invention has a relatively excellent effect.
Claims
1. A positive lead paste for deep discharge high cycle lead-acid battery, comprising lead powder and additives, characterized in that: Based on 100 parts by weight of lead powder, the additives include 0.05-0.2 parts of porous carbon microbeads, 0.08-0.15 parts of carbon whiskers, 0.5-1.5 parts of white carbon black, 0.3-1 parts of sodium carboxymethyl cellulose, 0.1-0.5 parts of sodium perborate, 0.1-0.5 parts of tetrabasic lead sulfate, 0.06-0.1 parts of stannous oxide, 0.08-0.15 parts of antimony trioxide, and 0.08-0.15 parts of polyester staple fibers.
2. The positive electrode lead paste for deep discharge high cycle lead-acid battery according to claim 1, characterized in that: Based on 100 parts by weight of lead powder, the positive lead paste for deep discharge high cycle lead-acid battery further includes 10 to 12 parts of water and 8 to 11 parts of sulfuric acid with a density of 1.4 g / mL.
3. The method for preparing the positive lead paste for deep discharge high cycle lead-acid battery according to claim 2, characterized in that: The following steps are involved: (1) dissolving sodium perborate, tetrabasic lead sulfate, stannous oxide, and antimony trioxide in a first dose of water, and homogenously mixing to obtain a first homogenous mixed solution having a particle size of less than 1 μm; (2) dissolving the porous carbon microbeads, white carbon black, sodium carboxymethyl cellulose, and carbon whiskers in a second dose of sulfuric acid, and mixing them uniformly to obtain a second homogeneous mixed solution; (3) After dry-mixing the lead powder and polyester staple fibers, add a third dose of water, then add the first homogenous mixed liquid and mix evenly under vacuum, then add the second homogenous mixed liquid and a fourth dose of sulfuric acid, mix evenly to produce a paste.
4. The method for preparing the positive lead paste for deep discharge high cycle lead-acid battery according to claim 3, characterized in that: In step (1), an ultrasonic emulsifier is used for homogenous mixing; during homogenous mixing, the parameters set for the ultrasonic emulsifier are: ultrasonic emulsifier frequency 20-40KHZ, amplitude range 50-80μm, cavitation intensity 3-5W / cm 2 , power 1000~3000W; The homogenous mixing temperature is 50-70° C., and the homogenous mixing time is 30-60 min.
5. The method for preparing the positive lead paste for deep discharge high cycle lead-acid battery according to claim 3, characterized in that: In step (2), a high-speed shearing machine is used for uniform mixing. During mixing, the mixing temperature is 50 to 70° C., the high-speed shearing machine is maintained at a rotation speed of 2500 to 3500 rpm, and the high-speed shearing is performed for 150 to 250 minutes.
6. The method for preparing the positive lead paste for deep discharge high cycle lead-acid battery according to claim 3, characterized in that: In step (3), the pressure of the vacuum state is 0.05-0.06 MPa; The paste temperature is not higher than 45℃.
7. The method for preparing the positive lead paste for deep discharge high cycle lead-acid battery according to claim 3, characterized in that: The volume ratio of the first dose in step (1) to the third dose in step (3) is 2:8-10; The volume ratio of the second dose in step (2) to the fourth dose in step (3) is 2:6-9.
8. A positive electrode plate for a deep discharge high cycle lead-acid battery, using the positive electrode lead paste for a deep discharge high cycle lead-acid battery according to claim 1 or 2.
9. A lead-acid battery comprising a positive plate, a negative plate, a separator and an electrolyte, characterized in that: The positive electrode plate is the positive electrode plate for a deep discharge high cycle lead-acid battery as claimed in claim 8.
Citation Information
Patent Citations
Negative electrode lead paste of lead storage battery, negative electrode plate and lead storage battery
CN113394400A
Positive electrode lead paste of lead storage battery, positive electrode plate and storage battery
CN116207251A
Cited By
Recyclable valve-regulated lead-acid storage battery, lead paste and preparation method of lead paste
CN121885551A